Floristic and climatic changes at the Balingian Province of the Sarawak Basin, Malaysia, in response to Neogene global cooling, aridification and grassland expansion - Sia, Say-Gee; Abdullah, Wan Hasiah; Konjing, Zainey; John, Jaithish (Elsevier, 2019)
The floristic and climatic changes at the onshore part of the Balingian Province of the Sarawak Basin in response to Neogene global cooling, aridification and grassland expansion were reconstructed in this study. We carried out palynological and petrographical studies on coal samples collected from the Early Pliocene Begrih Formation and the Late Pliocene Liang Formation. We compared these results with the available floristic and climatic data of the Early Miocene Balingian Formation to explore possible changes in vegetation and climate. The study results suggested that though there was increased seasonality or reduced rainfall as a result of Neogene global cooling and aridification, the onshore part of the Balingian Province had experienced everwet climates, and the flora in this region had changed from predominantly Kerangas forest during the Early Miocene to the species-rich peat swamp forest during the Early and Late Pliocene.